CONTROL OF PREEXISTING FAULTS ON GEOMETRY AND KINEMATICS IN THE NORTHERNMOST PART OF THE JURA FOLD-AND-THRUST BELT - Ustaszewski K.; Schmid S.M. (My University, 2006)
This study investigates the formation of the northernmost anticlines of the late Miocene to early Pliocene thin-skinned Jura fold-and-thrust belt and provides evidence that a transition to thick-skinned tectonics did occur in this particular area during the late Pliocene. The northernmost anticlines of the Jura fold-and-thrust belt are characterized by pronounced along-strike asymmetries that were predetermined by a fault pattern inherited from Paleogene Upper Rhine Graben rifting. This fault pattern had disrupted the Triassic basal décollement of the Jura Mountains and controlled the nucleation of thrusts and folds, as well as transfer zones during the generally (N)NW directed transport of the detached sedimentary cover. Sinistral, transpressive oblique ramps nucleated along Paleogene, NNE trending basement normal faults and led to a northward protrusion of the Jura front, encroaching onto the southernmost Upper Rhine Graben. Shortening across the frontal anticlines is greatest along the oblique ramps and decreases along strike toward the east, necessitating a gentle clockwise rotation of the detached sediments. Despite the fact that the stress field in the sedimentary cover remained unchanged, thin-skinned folding and thrusting came to a halt in the early Pliocene, giving way to thick-skinned tectonics, very probably governing neotectonic activity in the area. This transition might represent a geodynamic reorganization of the northwestern Alpine foreland. Copyright 2006 by the American Geophysical Union.
Keywords: Paleogene; Triassic; Pliocene; Miocene; Cenozoic::Paleogene; Кайнозой::Палеоген; Mesozoic::Triassic; Мезозой::Триасовая; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен